Conservation Challenges for Endangered Mammals: Research Gaps and Collaboration Needs Based on Stakeholder Bibliometric Analysis - Novriyanti; Buchori, Damayanti; Masy'ud, Burhanuddin; Soekmadi, Rinekso (Jurnal Sylva Lestari, 2025)
The global focus on endangered mammals highlights urgent, effective conservation strategies addressing habitat destruction, land-use changes, poaching, agricultural expansion, and encroachment. This study aims to identify research gaps in stakeholder engagement, map research trends and assess leading contributors of endangered mammal conservation, and explore opportunities for international collaboration for biodiversity conservation. This study was done using bibliometric analysis of 716 initial documents that were further selected to 85 publications based on PRISMA guidelines in R-Studio tools. This review highlights the fact that there is a limited focus on stakeholder engagement within mammal conservation research. Countries with high biodiversity, such as Indonesia, Mexico, and Brazil, contribute less to the scientific literature than high-income countries. This imbalance suggests the need for equitable research funding and expanded collaboration. Strengthening partnerships with research-intensive countries could increase publication output and knowledge sharing. Furthermore, regional cooperation with other original countries with similarly endangered species, like Malaysia and Thailand, is essential for improving research quality and optimizing resource exchange. The findings further highlight the importance of sustainable conservation practices and stakeholder engagement in effectively fostering the protection of endangered mammal species. Keywords: conservation governance, endangered species, research partnership, stakeholder engagement, systematic literature review